2021
DOI: 10.1039/d1ra06799k
|View full text |Cite
|
Sign up to set email alerts
|

New quinoxaline compounds as DPP-4 inhibitors and hypoglycemics: design, synthesis, computational and bio-distribution studies

Abstract: The current work represents the design and synthetic approaches of a new set of compounds 6–10 bearing the 1,4-dimethyl-2,3-dioxo-1,2,3,4-tetrahydroquinoxaline-6-sulfonamide scaffold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 79 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…43 A biodistribution study was rendered for one of the hopeful antimicrobial candidates 6b as a representative example to explore its in vivo pharmacokinetic behavior and body organ uptakes, besides its elimination pathway via radiolabeling with 131 I. 44,45 2.3.1. Radiolabeling of the Compound 6b.…”
Section: Dhfr Inhibitory Efficiencymentioning
confidence: 99%
“…43 A biodistribution study was rendered for one of the hopeful antimicrobial candidates 6b as a representative example to explore its in vivo pharmacokinetic behavior and body organ uptakes, besides its elimination pathway via radiolabeling with 131 I. 44,45 2.3.1. Radiolabeling of the Compound 6b.…”
Section: Dhfr Inhibitory Efficiencymentioning
confidence: 99%
“…Molecular docking studies were performed with the most promising candidates 45 a, 46 a, 47 a, and 47 b where all the compounds displayed good binding with the active pockets of DPP-4 (PDB ID: 3WQH). [42] Triloknadh et al, described the design, synthesis, in silico docking studies and biological evaluation of novel quinoxalinehydrazide hydrazone-1,2,3-triazole hybrids as α-glucosidase inhibitors (48 and 49, Figure 13). All the synthesized compounds 48 and 49 were screened for in vitro α-glucosidase inhibitory activity and the results showed that analogs 48 a-48 c and 49 a were the most potent candidates of the series with IC 50 values of 21.92, 22.32, 23.58, and 24.50 μg/mL, respectively when compared with reference drug acarbose (22.32 μg/mL).…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…Further, synthesized compounds were evaluated for in vivo anti‐hyprglycemic effect by intraperitoneal glucose tolerance test (IPGTT) where results unveiled that compounds 46 a , 47 b and 47 a were the most potent compounds. Molecular docking studies were performed with the most promising candidates 45 a , 46 a , 47 a , and 47 b where all the compounds displayed good binding with the active pockets of DPP‐4 ( PDB ID: 3WQH ) [42] …”
Section: Pharmacological Activities Of Quinoxaline‐based Compoundsmentioning
confidence: 99%
“…Omarigliptin is also a DPP-4 inhibitor with a sulfonamide portion, as depicted in Figure 1 . Omarigliptin is distinct from other antidiabetic drugs since it has a long half-life, may be taken orally, and only needs to be dosed once every seven days [ 46 ].…”
Section: Introductionmentioning
confidence: 99%